Delays in phases of care from identification to treatment of suspicious lung nodulesCentral MessagePerspective - Nihar Rama, BS; Rachel Nordgren, PhD; Aliya N. Husain, MD; Aditya Juloori, MD; Christine M. Bestvina, MD; Rajat Thawani, MD; Marina Garassino, MD; Septimiu Murgu, MD; Ajay Wagh, MD, MS; D. Kyle Hogarth, MD; Carrie Barth, MS; Darren Bryan, MD; et al. (JTCVS Open)
Objectives: Shorter time to lung cancer diagnosis and treatment is associated with improved outcomes. We analyzed the time spent from nodule identification to treatment to identify targets for improving the timeliness of suspicious lung nodule care in a diverse patient population. Methods: This was a retrospective cohort study of patients with suspicious lung nodules (suspected clinical stage I/II primary lung cancer) at a single academic medical center (2020-2022). Patients with suspected stage III/IV or nonprimary lung cancers were excluded. Multivariable Cox regressions were performed to assess factors associated with timeliness of care. Results: Of 157 patients, 59% were female, 53% were Black, and mean age was 70 ± 8.6 years. Nodules were identified incidentally (52%) or via screening (48%). Treatment was surgery in 52% and stereotactic body radiotherapy in 44%, and 10.2% were benign. Median (interquartile range) times from referral to diagnosis and from referral to treatment were 34 (22-56) days and 65 (44-84) days, respectively. Consultation to biopsy (20 [12-34] days) and diagnosis to treatment (28 [8-43] days) were the longest phases of care. Longer time from referral to diagnosis was associated with Black race and widowed status, whereas longer time from referral to treatment was associated with female gender, widowed status, frailty, body mass index greater than 18.5, Eastern Cooperative Oncology Group performance status less than 2, bronchoscopic biopsy, and treatment with stereotactic body radiotherapy. Conclusions: Increased time spent in suspicious lung nodule care is associated with demographic, social, and clinical factors. The longest phases are time from consultation to biopsy and from diagnosis to treatment. Improving multidisciplinary care coordination for vulnerable patient populations could improve the timeliness of suspicious lung nodule care.